2017
DOI: 10.24251/hicss.2017.336
|View full text |Cite
|
Sign up to set email alerts
|

Public-Private Collaboration in the Emergence of a National Electronic Identification Policy: The Case of NemID in Denmark

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 40 publications
0
22
0
Order By: Relevance
“…Finally, we must emphasize that our investigation of challenges with data governance is limited to the views within local government organizations. Involving citizens is a very important direction for future data governance research, and also a well-known problem in the e-government literature (Medaglia 2012;Medaglia et al 2017;Olphert and Damodaran 2007;. With the instatement of GDPR,…”
Section: Implications and Suggestions For Future Researchmentioning
confidence: 99%
“…Finally, we must emphasize that our investigation of challenges with data governance is limited to the views within local government organizations. Involving citizens is a very important direction for future data governance research, and also a well-known problem in the e-government literature (Medaglia 2012;Medaglia et al 2017;Olphert and Damodaran 2007;. With the instatement of GDPR,…”
Section: Implications and Suggestions For Future Researchmentioning
confidence: 99%
“…Some studies found that PPPs are a fundamentally new organizational form [27], and the frictions among the partners in this new organizational form may lead to vital issues and unintended consequences [11]. Therefore, further discussion on the management of such structures has been carried out to investigate the governance mechanisms in PPPs [24]. However, governance issues associated with the PPP project in the context of smart cities are often more complicated compared with the ones in the E-government, which, therefore, need to be addressed in further research.…”
Section: Public-private Partnerships (Ppps)mentioning
confidence: 99%
“…One such interaction point is the establishment of electronic identification systems (Whitley and Hosein, 2008;Grönlund, 2010), used both by the financial sector and the public sector (Medaglia et al, 2017). Official systems for the authentication of citizens, such as identification cards, have traditionally been the exclusive responsibility of state bureaucracies.…”
Section: Introductionmentioning
confidence: 99%